Análise comparativa de indicadores de carência habitacional urbana: Fundação João Pinheiro, Fundação SEADE e HABITAT/ONU - Barbo, André Roriz de Castro (2005)
Identifying the several improper forms of dwelling is fundamental to permit the definition of priorities by the public specialized agencies, as building of new residence demands high investments. For this purpose, it is essential to stimulate a rigorous methodological discussion, with the spread of indicators, components and concepts used in the identification of housing needs. In this sense, the present dissertation intends to discuss the calculation of urban housing needs in Brazil through the study of three housing need indicator systems, two of them developed by Brazilian official agencies - the Fundação João Pinheiro and Fundação SEADE and one developed by an international organization - the United Nations Human Settlements Programme (HABITAT). The general objective of this work is to analyze the three indicator systems in a comparative way aiming a methodological improvement and, the specific objectives are to identify the housing needs evaluated by each one of them and to compare the indicators used based on criteria previously defined. In result, it was possible to confirm that the three methods of calculation identify similar housing needs, however using different indicators.